The reproductive biology of Diplodus argenteus (Sparidae) in the coastal upwelling system of Cabo Frio, Rio de Janeiro, Brazil - David, G. S.; Coutinho, R.; Quagio-Grassiotto, I. [UNESP]; Verani, J. R. (My University, 2005)
The reproductive biology of the seabream Diplodus argenteus, a dominant coastal fishery species, was investigated over two consecutive seasons (2001-2002) at Cabo Frio, Brazil, a low-latitude upwelling system. The sex ratio was dominated by females (1.4:1.0) and the length-at-50% sexual maturity (females) was 203mm total length. Females were multiple spawners and the reproductive pattern appeared to be digynous protandrous hermaphroditism. Monthly variations in gonadosomatic index and proportion of ripe females indicated that reproductive activity occurred from late winter to summer (August-February), following coastal upwelling. Copyright © NISC Pty Ltd.
Keywords: Diplodus; Reproduction; Seabream; Sparidae; Upwelling; fish biology; reproductive biology; upwelling; Brazil; Cabo Frio; Rio de Janeiro [Brazil]; South America; Diplodus argenteus